2013
DOI: 10.1155/2013/378492
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Biofilm Forming Ability in Staphylococci Causing Bovine Mastitis Using Phenotypic and Genotypic Assays

Abstract: A total of 40 S. aureus and 68 coagulase negative Staphylococcus (CNS) isolates from bovine subclinical mastitis were investigated for their ability to form biofilm as one of the most important virulence factors.Using Congo Red Agar (CRA) method, 32.5%, 35%, and 32.5% of S. aureus strains were strong, intermediate, and negative biofilm producers, while in CNS the percentages were 29.5%, 42.6%, and 27.9%, respectively. By microtiter plate (MTP) method, 52.5%, 27.5%, and 20% of S. aureus isolates were strong, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
68
4
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 38 publications
20
68
4
4
Order By: Relevance
“…The results of this study and previous studies indicate a high prevalence of the icaA/D genes among staphylococci isolates, and that their presence is not necessarily associated with in-vitro formation of biofilm (36). In the current study, the proportion of S. epidermidis isolates that were positive for icaA/D genes in PCR method was higher than the proportion of those that were positive in CRA method.…”
Section: Discussionsupporting
confidence: 49%
“…The results of this study and previous studies indicate a high prevalence of the icaA/D genes among staphylococci isolates, and that their presence is not necessarily associated with in-vitro formation of biofilm (36). In the current study, the proportion of S. epidermidis isolates that were positive for icaA/D genes in PCR method was higher than the proportion of those that were positive in CRA method.…”
Section: Discussionsupporting
confidence: 49%
“…No sample was positive for icaA, but seven (21.8%) samples were only positive for icaD, suggesting that biofilm can be formed even when only one ica loci gene is present. These results are like those obtained by Darwish and Asfour (2013) with bovine milk samples. These authors observed prevalence rates of icaA and icaD genes of 15.0 and 62.5%, respectively.…”
Section: Phenotypic and Genotypic Biofilm Productionsupporting
confidence: 89%
“…Although, other authors reported lower sensitivity and specificity of CRA biofilm detection (Taj et al, 2012;Darwish and Asfour, 2013), and also this test may not be reliable for detection of biofilm (Taj et al, 2012), in this study, this test demonstrated a good correlation with gold standard microtiter assay. Biofilm producer samples were found to be simultaneously positive for the presence of icaA and icaD genes in nine (28.1%) of the 32 samples.…”
Section: Phenotypic and Genotypic Biofilm Productioncontrasting
confidence: 60%
See 1 more Smart Citation
“…CoNS are normal inhabitant of udder skin, teat canal and milkers' hand; thus, they are regarded as opportunistic, nosocomial and emerging pathogen Taponen and Pyorala, 2009;El-Jakee et al, 2013). Effectiveness of antibiotic therapy to treat bovine mastitis has been demonstrated to be compromised due to induction of antibiotic resistance and formation of biofilms which can be produced by both CoPS and CoNS Darwish andAsfour, 2013: Tiwari et al, 2013;Al-Rubaye et al, 2016). Among many reasons behind failure of successful treatment of bovine mastitis, one is the failure of appraisal of the antimicrobial resistant pattern of pathogens involved (Du Preez, 2000).…”
Section: Introductionmentioning
confidence: 99%